Construction of Taijiquan teaching mode for international students based on WeChat public platform - Song, Bo; Xie, Shiguang (The Journal of the International Society of Chinese Health Practices, 2021)
Objective: With the continuous improvement of my country's comprehensive national strength and the steady development of higher education, my country's higher education institutions have increasingly frequent foreign exchanges, and the education of foreign students has become an important part of higher education. Taijiquan teaching for international students in colleges and universities is one of the important ways for the international development of martial arts. It helps to improve my country’s cultural soft power and external competitiveness. It has a significant role in promoting my country’s cultural "going out" and the construction of world-class universities. The emphasis on Tai Chi teaching for foreign students. However, related studies have shown that traditional Taijiquan teaching methods for foreign students have problems such as single teaching methods, lack of corresponding teaching materials, insufficient modern technology and multimedia applications, etc. , resulting in the phenomenon that foreign students are not interested in learning Taijiquan and the teaching effect is not obvious; On the one hand, the use of WeChat has become an indispensable item in the life of international students in China. Reviewing the status quo of Taijiquan teaching for foreign students, it is necessary to combine new media and network technology to build a platform for learning Taijiquan for foreign students, to give full play to its immediacy, interactive, and diverse characteristics, to enrich the learning styles of Taijiquan for foreign students, and to optimize learning methods. The construction of learning platform based on WeChat has gradually attracted the attention of related scholars in the field of education technology, but there are fewer applications for the construction of Taijiquan teaching platform, and the related research on the group of international students is even more inadequate. In order to improve the quality of Taijiquan learning for international students, enrich the learning methods, and maximize the application value of WeChat in the process of Taijiquan learning, continuous attention should be paid to the construction and research of the Taijiquan learning platform for international students. Methods: Using literature, logical analysis and other research methods, through searching and purchasing related books in the library, a total of 23 books related to platform construction and teaching of foreign students were found. This article has referenced 12 of them and cited 8; through China CNKI and other data The platform searches sports, pedagogy, communication and other related literatures. Through screening and selection, 84 literatures are finally selected as research materials, and 13 of them are cited, which provides strong theoretical support for the smooth progress of the research. Results: According to the research, the advantages of the Taijiquan learning platform for international students are mainly the following four points. First of all, it can solve the obstacles of language communication. On the one hand, foreign students are quite different from Chinese students in culture and language, and there is less communication between students. On the other hand, there are not many Tai Chi teachers who can use bilingual teaching, which greatly affects the communication and interaction between the two sides. Language communication barriers are the main obstacles in the process of learning Taijiquan for foreign students, which seriously affects the learning effect of foreign students. Due to the inability to communicate effectively and the mastery of technology, foreign students just stay at the surface and cannot touch the deep core of Chinese culture. Through the display of Chinese and English bilingual learning content on the learning platform, combined with the teaching of pictures and videos, it provides richer perceptual materials for international students' Tai Chi learning, solves language communication barriers, stimulates international students' interest in learning, and improves the effect of learning. Second, it is possible to use "fragmented" time to learn. The WeChat learning platform establishes a connection with international students through mobile terminal equipment, so that international students’ Tai Chi learning is not limited by time and space, and can make full use of the “fragmented” time of international students, whether it is by bus, subway, or before going to bed. You can check and learn through mobile terminal devices such as mobile phones. Make full use of the "fragmented" time, and all the pushed content of the learning platform can be forwarded and collected, which is more conducive to the repetitive learning of international students. Again, it can be used as a supplement to the traditional teaching model. The traditional teaching mode of Taijiquan for international students is based on the classroom. Whether it is based on language explanations, or based on intuitive perception of movement demonstration methods, and based on physical exercises, it is all through the teaching method. During the process, technical exercises are continuously carried out to achieve the predetermined teaching goals and requirements. Ignoring the students' mastery and deepening of the learning content after class, leading to the phenomenon of forgetful actions, and unable to achieve the expected teaching goals. The WeChat-based Taijiquan learning platform for international students can not only consolidate the teaching content of the classroom, but also enable international students to learn more in depth according to different needs, and receive more knowledge and information outside the classroom, which is a supplement to the traditional teaching model. Finally, it can reduce the cost of studying for international students. WeChat learning is different from the traditional learning method that requires the purchase of paper books and video materials. International students obtain the teaching content sent in the background through mobile terminals, and save important content permanently by means of text copy, picture download, etc. Through the learning platform with rich resources and interactive functions, international students can pass through the platform in a personalized way according to their own characteristics. Choosing suitable learning resources reduces the investment of foreign students in learning costs. Conclusion: The research further pointed out the guiding ideology and principles of platform construction. In the guiding ideology, the starting point should be to meet the learning needs first. The ultimate goal of platform construction is to better promote the learning of Tai Chi for international students. Therefore, the construction of the platform should meet the learning needs of international students as the starting point and provide a good online learning environment for international students, enriched by various texts, pictures, audios, videos, etc. Diverse teaching resources meet the learning needs of international students and arouse their interest in learning. Secondly, the goal should be to enhance the learning effect. In the traditional teaching model of Taijiquan for foreign students, due to language communication barriers, poor teaching conditions, and insufficient teaching materials, some students' interest in learning is reduced, which affects the formation of learning effects. Such problems can be effectively compensated through the learning platform. Students can log on to the platform at any time and anywhere to learn what they are interested in, and conduct in-depth learning based on the platform's professional pictures and video teaching, which is helpful to realize the diversity of learning activities. Transformation, cross-temporal and spatialization, break through the monotonous teaching activities in the traditional classroom, thereby turning passive into active, improving the initiative and consciousness of learning, and better enhancing the learning effect of Taijiquan for foreign students. The principle of autonomous learning, the principle of humanity and the principle of authenticity are the main principles of platform construction. In the traditional teaching field of Taijiquan for foreign students, the teaching and recitation of Taijiquan knowledge and repeated training of Taijiquan techniques are the main forms of classroom teaching. Different from the passive learning method in traditional Taijiquan teaching, with the help of the Taijiquan learning platform for foreign students, students can actively participate in the whole process of Taijiquan teaching and become the main body of learning. In the process of building a learning platform, it truly reflects the student's dominant position, and gives full play to the initiative and autonomy of overseas students. Considering that some international students have low Chinese proficiency and cannot operate more complex online learning systems, the platform system interface should be concise and generous, navigation should be clear and accurate, and the operation should be simple and easy to use. In the setting of learning content, the bilingual mode of Chinese and English is used to reduce the use of the platform. Degree of difficulty.